Ukrainian Refugees in Germany: A Hidden Conflict of Interests is Inevitable but Solvable - Taras Romashchenko (Einblicke / Insights: Forschungs-Highlights der Zentren für Deutschland- und Europastudien, 2024)
The full-scale war that Russia after more than 1.5 years still hasn't announced to Ukraine has changed the lives of Ukrainians forever. Since the end of February 2022, the peaceful country in the heart of Europe and its citizens have witnessed at large scale the ugly deaths, horrific injuries, unimaginable suffering and unbelievable destruction of numerous cities, towns and villages. There hasn't been anything like this on the European continent since World War II. Moreover, the Russian invasion has forced millions of Ukrainians to flee their homes in search of salvation, including abroad. According to recent estimations, Europe took the majority of them – 5.8 million out of 6.2 recorded globally. In this context, Germany's role can hardly be overestimated. Until now, the country has provided shelter for almost 1.1 million Ukrainians. Among EU countries only Poland can boast more – 1.6 million.
Keywords: 300; refugees; forced migrants; labour market; conflict of interests; Germany; Ukraine